Mobilized Indigenous Memories: An Analysis of the Production Process of Historical-Anthropological Reports of the Territorial Survey of Indigenous Communities in Río Negro,Argentina (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
In the past few years the national state has deployed different actions to recognize the rights, peculiarities and claims of the original peoples, elaborating different public policies, programs and projects. Notable among them for its national scope is the sanction of Law 26.160, and its program for the territorial survey of indigenous communities (ReTeCI) that intends to understand the current territo- rial situation of indigenous communities in the country. Focusing on the context of the execution of the survey in the province of Rio Negro, this article aims to address memory (stories, silences, concealments and reconnections) as a theoretical and methodological tool to enable new frameworks of interpretation that contributed to disputing, expanding and shaping the limits and foreseen effects of this public policy. From this perspective, the article analyzes the procedure of compliance with one of the components of the Technical Fol- der (TC), focusing on the construction of the Anthropological Historical Report (IHA) in order to expose the deployment of multiple effects generated by different reconnections. The prior is in order to deconstruct certain regional (and national) prejudices introduced around the suspicions of inauthenticity and instrumentalism that fall and are projected on indigenous peoples and their communities today; prejudices that consider finding new sustenance in the explosion of auto identification occurring in the framework of the survey
Keywords: Memory, Public Policies, Reconnections, Indigenous Peoples, Law 26.160